From alternative media to citizens’media: theoretical development of a new term: trayectoria teórica de un término - Rodríguez, Clemencia (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This article presents an analysis of the term ‘citizens’ media.’ The analysis examines how this term is rooted in the Latin American cultural studies tradition and how it emerges from Chantal Mouffe’s theory of radical democracy. Finally, the article presents different studies of community/alternative/indigenous media that use citizens’ media theory.